The Oil and Gas Industry in Asia: Fuelling Growth at a Cost - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2007)
According to the BP Statistical Review of World Energy 2007, China alone accounts for 15% of global energy consumption and 70% of growth in the consumption of coal. The review describes "robust demand" for oil and gas in Asia overall despite high prices. Dennis Ang, president of Statoil Asia Pacific, the Singapore based affiliate of Norway's largest company, shares his views with Knowledge@SMU on global energy issues, the environmental impacts of Asia’s fast growing demand for energy, and how the region could do more to move towards a`greener’ future.